PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Dwi Rachmawati; Dahlia Br Pinem (EQUITY, 2015)
This study was conducted to examine the effect of Profitability, Leverage and Firm Size on Firm Value at the Company's  anufacturing base and chemical industry sectors listed in Indonesia Stock Exchange during the years 2013 to 2014. The population in  his study amounted to 55 companies manufacturing industrial  ector basic and chemical contained in the Indonesia Stock Exchange during 2013 to 2014. Samples were obtained in this study of 52 samples selected by purposive sampling method. After outlier data, which eventually resulted 48 samples to be analyzed and tested. Data were tested using multiple linear regression method. These  esults showed that: Provitability significant positive effect on firm value, Leverage not significant effect on firm value and Firm Size positive effect on firm value.